Developing the teaching factory learning media in a public vocational high school - Sintha Wahjusaputri; Elin Marlina; Siti Latifah (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
This study aims to determine the success factors of the learning media of tutorial and skill e-report portfolios video-based in teaching factory learning outcomes in vocational high school. This study was the Research and Development model, through several stages, namely: (1) collecting data; (2) planning; (3) developing draft; (4) conducting initial trials; (5) revising the trial results; (6) conducting trial site research; (7) improving the productivity of the test results, (8) conducting test, (9) completing the final product; and (10) disseminating and implementing the result. This study was conducted at 58 Public Vocational High School, Jakarta. The samples were random sampling, consisting of 59 students majoring in painting and visual communication design in the control class and the experimental class. The instrument was a multiple-choice test sheet (multiple choice) through pre-test and post-test. The results of the study were analyzed using a t-test. The t-test average of the experimental class, Visual Communication Design, was 11.522. The t-test average of the control class was 10.832. Thus, the average learning outcomes of the experimental class were 0.69, which is bigger than in the control class. In the experimental class, Painting Class, the average learning outcome was 67, and the control class was 54.5. Therefore, there was a difference of 12.5. The hypothesis stated that there were differences in teaching factory learning resulted from the pre-test and post-test experimental classes majoring in Painting and Visual Communication Design. The instructional media of Tutorials and Skill E-Report Portfolio Video-Based got very good responses from students.